Efektivitas Pengembangan Bahan Ajar Berbasis Entrepreneurship: Tinjauan Sistematis - Entik Suticha; Zaenal Abidin (Peneliti.net, 2022)
Teachers play an important role in creating a learning atmosphere so that teachers and students together can carry out a conducive learning and teaching process so that the objectives of learning can be achieved. For this reason, teacher competence is needed in order to create a comfortable learning atmosphere and a joyful learning in the classroom. Therefore, an interesting learning strategy is needed for students to meet the challenges of the 21st Century. Currently, the development of an entrepreneurial spirit through formal education is an actual topic to be discussed. This is due to several very rational reasons. One of the reasons is that there are still many graduates of primary or secondary education who cannot continue their education to college. While they do not have sufficient provisions to enter the world of work. This study aims to examine the effectiveness of the development of entrepreneurship-based teaching materials. The method used in this study is a systematic review. This was carried out following the Preferred Reporting Items Guidelines for Systematic Review and Meta-Analysis (PRISMA). Of the 8 articles that were used as a systematic review, developing teaching materials had an impact on improving the development of students' abilities. Thus, it can be said that the development of teaching materials, especially entrepreneurship-based teaching materials, is effectively applied in learning.